Glycemic Control, Complications, and Sleep Quality in Type 2 Diabetes Mellitus: A Multivariate Analysis Using Logistic Regression - Jubir Jubir; Hilma Dentalistya Dentalistya; Riyan Mulfianda (STIKep PPNI Jawa Barat, 2026)
Background: Diabetes mellitus is a silent killer, meaning it kills people slowly. This disease can cause complications for sufferers, including reduced sleep quality due to factors that increase blood sugar levels, the emergence of other complications, psychological factors such as anxiety and stress, and providing family support for those with diabetes mellitus. Objective: The aim is to influence of sleep quality in patients with type 2 diabetes mellitus in Meuraxa Regional General Hospital, Banda Aceh City Methods: This study was a descriptive correlation study with a cross-sectional design. The population was 369 people, with a purposive sampling technique, resulting in a sample size of 79 individuals. A questionnaire was used as the data collection instrument. This study was conducted at Meuraxa Hospital, Banda Aceh City, and data analysis used the chi-square test. Results: The results of the study showed that 50 respondents (73.5%) had poor sleep quality compared to 18 respondents (26.5%). Based on the chi-square statistical test, the test used was Fisher's exact test on exact sig (2-sided) with a p-value of 0.005 (p < 0.05) and the results of the study showed that 51 respondents (83.6%) had poor sleep quality compared to 10 respondents (16.4%) who had good sleep quality. Based on the chi-square statistical test results, the test used was continuity correction on asymp sig (2-sided) with a p-value of 0.000 (p < 0.05). Conclusions: Type 2 diabetes mellitus can significantly affect a person's sleep quality and conversely, poor sleep quality can maintain the condition of type 2 diabetes mellitus